Azyumardi Azra's Middle-Path Islamic Politics: Anti-Violence and Democratization of Indonesia - Thaha, Idris; Fadhilla, Indah; Billahi, Savran; Suryani, Suryani (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. The phenomenon of violence in democratic countries such as Indonesia introduced a new angle in contextualizing modern Islamic political thought. The argument of mainstreaming fasad (violence or conflict) and islah (reconciliation) embedded in Islamic political thought preached by Azyumardi Azra as a part of the moderate Islam project (Islam wasathiyah) is considered a democratization process. This article seeks to examine Azyumardi Azra's thoughts in interpreting the concept of moderate Islam in the context of Indonesia's democratization, particularly regarding non-violence and social harmony. This article uses an interdisciplinary approach combining the interpretation of Islamic political thought, Middle-path political theory, and democratization analysis. It examines the Islamic revitalization formulating an anti-violence stance mainstreamed by Azyumardi that mediates the absolutist dogmatic beliefs and extremist political streams inciting violence. Finally, this article demonstrates how political thought embedded in Islam mainstreamed by Azyumardi benefits to strengthening democratization in Indonesia, moving away from violence.Keywords: Democratization, Middle-path Politics, Anti-violence, Revitalization of Islam, Wasatiyyah Islam.Abstrak. Kajian ini berfokus pada diskusi tentang pemikiran Azyumardi Azra dalam memaknai politik Islam jalan tengah (Islam wasathiyah) dalam upaya demokratisasi Indonesia, khususnya mengenai antikekerasan dan harmonisasi sosial. Dengan pendekatan Islam jalan tengah, ia berupaya mencari cara efektif mengatasi praksis kekerasan di Indonesia. Kajian ini menggunakan metode penelitian kualitatif dengan merujuk pada data-data primer melalui esai-esai dan buku-buku Azyumardi. Penelitian ini berhasil menganalisis pemikiran Azyumardi dalam merumuskan sikap antikekerasan sebagai gagasan revitalisasi Islam dengan menengahi keyakinan dogmatis absolut dan praksis politik ekstrem yang mendelegitimasi kekuasaan. Penelitian ini menyimpulkan, revitalisasi Islam yang dikemukakan Azyumardi merupakan cara efektif untuk mengatasi terjadinya kekerasan sebagai problematika demokrasi di Indonesia, kini dan di masa-masa mendatang. Kajian ini diharapkan dapat berkonstribusi bagi penguatan demokratisasi di Indonesia, yang jauh dari kekerasan.Kata Kunci: Politik jalan tengah, Islam wasathiyah, demokratisasi, revitalisasi Islam, antikekerasan.